Imaging Techniques for Survey of Book Collections - P. Vávrová; J. Neoralová; D. Novotná; M. Součková; D. Popelková; M. Matysová; T. Blecha; A. Kazanskii (Библиосфера)
Covers and book bindings, especially in library collections, may serve as an important hidden information source for researchers and readers. The article describes the experience of the National Library of the Czech Republic, its Collection Preservation Division, in testing of the X-ray system and Video spectral comparator VSC 8000 to apply non-destructive methods in exploring materials and damages in different layers of the books, and shows its advantages. The systematic evaluation of the X-ray system on the typical examples of book materials of different time-periods showed, that non-destructive radiological methods of book investigation can detect problematic materials and conditions of their destruction beforehand not only in material itself, but in the entire object – the book. It showed that the hidden information can be obtained without breaking or damaging of top layers. Moreover, these materials can be older than the book itself. Video spectral comparator is applied on nonvisible, uneasily recognizable texts, for example faded by light, mechanical or other principle of damage. Thus, gained information serves for historical, art, and scientific knowledge of book binding and texts.